Main factors associated with the violation of the criminal law committed by adolescents in the judicial district of Tacna. 2013-2016. - Fuentes Fuentes, Pierann Del Rosario (2020)
Analyzes the problem of juvenile delinquency, aiming to determine the main factors associated with the crime Infraction of the criminal law committed by adolescents in the judicial district of Tacna, 2013-2016. The hypothesis of the study was: In the Judicial District of Tacna, the main factors that are associated with the infraction of the criminal law committed by adolescents, 2013- 2016, are: social, economic and legal. We used the basic research method with non-experimental cross-sectional design. The study covered a population of 36 sentenced criminal offenses during the period 2013-2016, as well as 151 lawyers holding family cases and 07 Tacna family magistrates. Three measurement instruments were used for the information collection (questionnaire, Observation and interview). The results of the research allow to verify the proposed hypothesis of study